2016
DOI: 10.3349/ymj.2016.57.5.1152
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Regenerative Cell Injection Therapy for Postprostatectomy Incontinence: A Phase I Clinical Study

Abstract: PurposeWe report our initial experience with transurethral injection of autologous adipose-derived regenerative cells (ADRCs) for the treatment of urinary incontinence after radical prostatectomy.Materials and MethodsAfter providing written informed consent, six men with persistent urinary incontinence after radical prostatectomy were enrolled in the study. Under general anesthesia, about 50 mL of adipose tissue was obtained from the patients by liposuction. ADRCs were obtained by separation with centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…Magnetic resonance imaging showed a sustained presence of the injected adipose tissue, and enhanced ultrasonography showed a progressive increase in blood flow to the injected area in all patients. Thereafter, a Korean group treated six male SUI patients after RP following our procedure, and confirmed the improvement of subjective symptoms and quality of life, along with improved urethral sphincter function during a 12‐week follow‐up period …”
Section: Discussionsupporting
confidence: 54%
“…Magnetic resonance imaging showed a sustained presence of the injected adipose tissue, and enhanced ultrasonography showed a progressive increase in blood flow to the injected area in all patients. Thereafter, a Korean group treated six male SUI patients after RP following our procedure, and confirmed the improvement of subjective symptoms and quality of life, along with improved urethral sphincter function during a 12‐week follow‐up period …”
Section: Discussionsupporting
confidence: 54%
“…No significant peri‐ or postoperative adverse events were reported. Similar results were reported in a study of six post‐RP incontinent patients who were injected a mixture of ADSCs and adipose tissue into the rhabdosphincter and submucosal space . In a rat model replicating post‐RP SUI and erectile dysfunction (ED), Yiou et al delivered human multipotent ADSCs (hMADSCs) directly into the electrocautery‐damaged sphincter and penis.…”
Section: Scs In Male Incontinencesupporting
confidence: 61%
“…Thus, an ideal therapeutic modality for SUI would include revascularization, reinnervation, and striated muscle replenishment of the sphincter. Several preclinical studies have demonstrated various types of MSCs, injected periurethrally, to be efficacious . Most of these studies used rats or mice as animal models, and different techniques have been applied to cause SUI.…”
Section: Scs In Male Incontinencementioning
confidence: 99%
“…Swelling of the urethra immediately after application of aliquots summing up at a total volume of 1 mL did not change the urethral pressure profiles compared to the profiles acquired immediately prior to treatment. Moreover, to cause a bulking effect by cell injections, 20 mL of a suspension of autologous adipose‐derived cells were injected in the submucosal tissue of men . This is a considerably larger injection volume compared to the volumes applied in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of hydrogels or other components in the submucosa and close to the urothelium layer of the sphincter complex may cause local swelling or bulking effects as observed by our injection test employing cadaveric sphincter samples. This of course is beneficial when bulking is needed to treat SUI . In contrast, in case of a regenerative cell therapy, injections of smaller volumes in deeper zones may be beneficial, because regeneration of the contractile sphincter apparatus will be facilitated when the regenerative cells are deposited close by.…”
Section: Discussionmentioning
confidence: 99%